The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.frl.2021.101944
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on housing price: Evidence from China

Abstract: Using data on monthly community-level confirmed COVID-19 cases and housing price in China, we investigate the impact of COVID-19 on housing price. With the difference-in-difference method, we find that the housing price of the communities with confirmed COVID-19 cases would reduce by 2.47%. The impact persists three months and the extent of the impact basically becomes greater as time goes on. The results are robust after the parallel pre-trend test and the placebo test. Moreover, the impact of COVID-19 on hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 23 publications
5
70
1
1
Order By: Relevance
“…The results reveal that in communities with confirmed COVID-19 cases, there is a 2.47% fall in accommodation price, and the negative effect can continue for three months, with the scope of the effect actually increasing with time. The effect of COVID-19 on the accommodation price manifests only in the regions with higher COVID-19 infection levels or high mortality rates [80].…”
Section: Accommodation Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reveal that in communities with confirmed COVID-19 cases, there is a 2.47% fall in accommodation price, and the negative effect can continue for three months, with the scope of the effect actually increasing with time. The effect of COVID-19 on the accommodation price manifests only in the regions with higher COVID-19 infection levels or high mortality rates [80].…”
Section: Accommodation Pricesmentioning
confidence: 99%
“…Since the real estate industry plays an important role in the economy of the country, public authorities should focus more on the impact of COVID-19 on accommodation prices and implement a complementary real estate policy [80]. By using data about the confirmed community-level COVID-19 cases in a month and the accommodation price in China, we can analyze the impact of COVID-19 on the accommodation price.…”
Section: Accommodation Pricesmentioning
confidence: 99%
“…COVID-19 emerged as a pandemic in the first quarter of the year 2020 and had social ( Yezli and Khan, 2020 ), ecological ( Muhammad et al, 2020 ), political ( Kerr et al, 2021 ), and economic ( Qian et al, 2021 ) effects all over the world. At present, no internationally recognized measures are used as standards to cure COVID-19 patients ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In my research, in one of the analysed cities (Kraków) there were also dwelling price decreases (starting from Q2 2020) but the forecasting price dynamics showed possible decreases in two cities (Kraków and Gdańsk). In a similar study in China [59] using the difference-in-difference method, it has been shown that the impact of COVID-19 on housing price only exists in regions with a higher infection level of COVID-19. The research confirmed that the housing prices of the communities with confirmed COVID-19 cases are reduced by 2.47%.…”
Section: Literature Review With a Discussion Of Resultsmentioning
confidence: 99%